Penyuluhan Kewirausahaan Bagi Anggota Kelompok Karang Taruna Di Kelurahan Malaka Sari, Duren Sawit - Rahmi, Rahmi; Purwana, Dedi; Aditya, Shandy (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2019)
Getting a job has been more difficult nowadays due to the scarcity of job opportunities. The number of available manpower is much higher than the job vacancies. The incompatibility of expertise and difficulties to meet company’s requirement with suitable job seeker also increase the unemployment rate. This program is performed to stimulate young people to think creative innovative and eventually encourage them to start their own business as solution to the problem. The method used is explanation, experiences sharing, question and answer, discussion, and business plan presentation. Based on these activities, not only participants’ knowledge about entrepreneurship increases, but also their ability to create a product or business systematically is trained. Furthermore, capital issue is solved by providing alternatives of business form such as dropshipper, franchising, or joint venture. Last but not least, a message group is formed as a media to discuss, consult, and encourage each other to start a business or participate in business plan competition.